A tale of two hailings: driving behaviour and safety culture perceptions according to driver types and working hours - Mohd Mahudin, Nor Diana; Sakiman, Muhammad Nurhisam (2018)
The changing nature of ride-hailing services, which include traditional taxi services and e-hailing applications, are increasingly imposing concerns to the transportation industry. Previous research has shown marked differences in safety perceptions, attitudes, and behaviours among different types of driver and work conditions. However, it remains unclear how these perceptions, attitudes, and behaviours would be manifested differently by drivers in ride-hailing services given the hours they spent on the job. The present study investigated these gaps with 80 drivers (Taxi: n = 40; Grab/Uber: n = 40). Using the short version of the Manchester Driver Behaviour Questionnaire (MDBQ) and the Safety Climate Questionnaire (SCQ), the results indicated that Grab/Uber drivers reported a significantly higher safety climate perception scores than taxi drivers; but no significant difference between the two drivers was observed in unsafe driving behaviour scores. Meanwhile, analyses of variance demonstrated a significant effect of hours spent at work on safety climate perception and driving behaviour. In particular, the Tukey’s HSD tests showed that drivers who worked below 12 hours per week reported significantly more unsafe driving behaviour than those who worked between 13 to 36 hours and 61 hours or more. It was also found that drivers who worked below 12 hours per week reported significantly more positive safety climate perception compared with those who worked 61 hours or more. Safety climate perception scores for drivers who worked between 13 to 36 hours were also significantly higher than those who worked 61 hours or more. Further General Linear Model (GLM) analyses revealed the main effect of hours worked and an interaction effect of driver types and hours worked on unsafe driving behaviour scores. However, no main and interaction effects of driver types and hours worked on safety climate scores were significant. The present results are discussed in line with driving behaviour and safety climate research as well as in the future trends toward shared mobility.